DEVELOPMENT OF FLEXIBILITY QUALITIES IN PRE-SCHOOL EDUCATIONAL INSTITUTION STUDENTS THROUGH A SET OF SPECIALIZED TAEKWONDO EXERCISES - Iminova Z. B. (European Science Publishing, 2025)
In this article, it is noted that flexibility is one of the physical qualities and its use in martial arts. Flexibility is a characteristic of the musculoskeletal system, which determines the limits of movement of body parts. Two types of flexibility are distinguished: active flexibility, which is characterized by the values of the amplitude of movements performed independently as a result of muscle tension, and slow flexibility, which is achieved under the influence of external forces, and is characterized by the maximum characteristics of the amplitude of the movements.
Keywords: Sport, martial arts, taekwondo, flexibility, physical attributes, physical exercise, young children.